Development of Interactive Video Media in the Thematic Learning of Class IV SD Negeri 56 Lubuklinggau - Anggara, Bayu; Harmoko, Harmoko; Kusnanto, R. Angga Bagus (Widyagogik, 2022)
This study aims to develop interactive video media in valid and practical thematic lessons of various styles of material. This study uses a 4-D development model. The instruments used to measure the quality of the interactive video media developed include validation sheets, practicality questionnaires. The product of this research is in the form of interactive video media on thematic subject matter of various styles in grade IV. So the results of this study indicate that: First, the validity of the interactive video game media can be seen from the aspect of validity so that it is included in the valid category with an average score of 3.30; Second, the practicality of interactive video game media can be seen from the practical aspect so that it is included in the very practical category with an average score of 82.00.